PERAN GENDHING JATHILAN DALAM PROSES NDADI PADA KESENIAN JATHILAN KELOMPOK TURONGGO MUDO DESA BOROBUDUR - Muhammad Nur Salim (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2014)
This research is motivated on the phenomenon of ndadi in Jathilan Turonggo Mudo performance. Ndadi phenomena associated with the world of the cosmos and there are several steps that must be done to achieve it. One way to achieve ndadi conditions is the use of music. Music, which in this case is a gendhing Jathilan believed to help as a bridge in the process of achieving ndadi. This study aims to reveal the role of music as an element that supports ndadi conditions. Gendhing Jathilan became one of preconditions required the establishment of the relation. Ndadi in Jathilan performances occurs when gendhing jathilan is presented as a musical accompaniment. Nevertheless gendhing Jathilan is not create or form someone to ndadi but as a facilitator in delivering a dancer to experience ndadi. It is based on the gendhing Jathilan relation with the other context of ndadi. Gendhing Jathilan becomes a stimulus to bring a behavior called the ndadi. Gendhing Jathilan has the potential characteristics in ndadi conditioning process. The characters in addition to referring to the gendhing jathilan performance, also the form / structure of gendhing such as strophic form, ostinato, and repetitive. Gendhing Jathilan in the final round performances jathilan presented three times. In each of these perform have the respective roles in the process of ndadi. Gendhing Jathilan has some role in every phase of the ndadi process such as gendhing as a conductor of ndadi, gendhing as ndadi accompaniment and gendhing in healing of ndadi.Keywords: ndadi, role, characters, gendhing Jathilan